2020
DOI: 10.1038/s41598-020-59485-3
|View full text |Cite
|
Sign up to set email alerts
|

Bergamot Polyphenols Improve Dyslipidemia and Pathophysiological Features in a Mouse Model of Non-Alcoholic Fatty Liver Disease

Abstract: There is a need for continued drug development for nonalcoholic steatohepatitis (NASH). Bergamot is a plant whose fruit juice is enriched with flavonoids and phenolic compounds which improves dyslipidemia and markers of systemic inflammation in patients with Metabolic Syndrome. The aim of this study was to perform a preclinical "proof of concept" study of Bergamot polyphenolic formulation (BPF99) for the treatment of NASH. A disease reversal study was performed in the diet-induced animal model of NAFLD (DIAMON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…Many previous studies have shown that plant polyphenols, flavonoids, carotenoids, vitamins can effectively lower the level of TC, TG, LDL and MDA in hyper-cholesterolemic rodents [ 36 , 37 , 38 , 39 ]. The present results were following the findings of Musolino et al [ 40 , 41 ] that demonstrated that bergamot polyphenolic fraction (BPF) prevented the alteration of lipid profile in hypercholesterolemic rats, counteracting oxidative stress markers and also ameliorate the dysregulation of the lipoprotein metabolism; suggesting that the richness of antioxidant properties may play an important role in improving dyslipidemia.…”
Section: Discussionsupporting
confidence: 90%
“…Many previous studies have shown that plant polyphenols, flavonoids, carotenoids, vitamins can effectively lower the level of TC, TG, LDL and MDA in hyper-cholesterolemic rodents [ 36 , 37 , 38 , 39 ]. The present results were following the findings of Musolino et al [ 40 , 41 ] that demonstrated that bergamot polyphenolic fraction (BPF) prevented the alteration of lipid profile in hypercholesterolemic rats, counteracting oxidative stress markers and also ameliorate the dysregulation of the lipoprotein metabolism; suggesting that the richness of antioxidant properties may play an important role in improving dyslipidemia.…”
Section: Discussionsupporting
confidence: 90%
“…Flavonoids, commonly found in apples, grapes, onions, and herbs, exhibit potential beneficial effects on human health, including anti-allergic, antiviral, antioxidant, and anti-inflammatory activities, and they have been shown to have preventive and therapeutic effects against NAFLD [ 9 ]. Moreover, dietary flavonoid consumption improves dyslipidemia and decreases hepatic fat accumulation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific evidence shown that bergamot polyphenolic fraction (BPF) improves serum lipemic profile and modulates blood pressure in patients with metabolic syndrome (MetS), a state which contribute to the development of HF [31,32,33]. Previous scientific evidence obtained with citrus fruits, shown their beneficial effects and clarify some mechanisms involved in MetS [34,35].…”
Section: Bergamot Polyphenolsmentioning
confidence: 99%
“…The hypolipemic effect of BPF seems to be related to the modulatory properties of naringin and neohesperidin. Indeed, dietary hesperetin inhibits hepatic t ri acylglycerol ( TG) accumulation, w h i c h m a y b e associated with the reduced activity of TG synthetic enzymes, such as phosphatidate phosphohydrolase [33]. In addition, in vitro studies showed that naringenin and hesperetin decrease the availability of lipids for assembly of apoB-containing lipoproteins.…”
Section: Bergamot Polyphenolsmentioning
confidence: 99%